Jacob's Ladder Kabbalistic Allegory in Russian Literature - Aptekman, Marina (Borderlines: Russian and East European-Jewish Studies, 2011)
Jacob's Ladder discusses the reflection of kabbalistic allegory in Russian literature and provides a detailed analysis of the evolution of the perception of Kabbalah in Russian consciousness. Aptekman investigates the questions of when, how, and why Kabbalah has been used in Russian literary texts from Pre-Romanticism to Modernism and what particular role it played in the larger context of the Russian literary tradition. The correct understanding of this liaison helps the reader clarify many enigmatic images in Russian literary works of the last two centuries and to understand the roots of a particular cultural falsification that played an important role in the anti-Semitic mythology of the twentieth century.